A Novel Mutation in ACTG2 Gene in Mother with Chronic Intestinal Pseudoobstruction and Fetus with Megacystis Microcolon Intestinal Hypoperistalsis Syndrome - Julie R. Whittington; Aaron T. Poole; Eryn H. Dutta; Mary B. Munn (Case Reports in Genetics)
Background. A novel mutation in the ACTG2 gene is described in a pregnant patient followed up for chronic intestinal pseudoobstruction (CIPO) during pregnancy and her fetus with megacystis microcolon intestinal hypoperistalsis syndrome (MMIHS). Case. 24-year-old gravida 1 para 1 with CIPO and persistent nausea and vomiting in pregnancy, admitted at 28 weeks of gestation. Ultrasound revealed a fetus measuring greater than the 95th percentile, polyhydramnios, and megacystis. At delivery, the newborn was noted to have an enlarged bladder, microcolon, and intolerance of oral intake. Genetic testing of mother and child revealed a novel mutation in the ACTG2 gene (C632F>A, p.R211Q). Conclusion. This is the first case in the literature describing a novel mutation in ACTG2 associated with visceral myopathy affecting both mother and fetus/neonate. Visceral myopathy should be included in the differential diagnosis of megacystis diagnosed by ultrasound, and suspicion should increase with family history of CIPO or MMIHS.